MODIFICATION OF PHYSICOCHEMICAL PROPERTIES FISETIN THROUG SPHERICAL CRYSTAL TECHNIQUES - Dzakwan, Muhammad (P3M STIKes Bakti Tunas Husada, 2019)
Fisetin is a natural antioxidant that has shown to posses antioxidant and anti-inflammatory. However, the poor solubility leads to poor bioavailability and limits its development. Fisetin spherical agglomerates were prepared with ethanol, water, chloroform and polyvinylpyrrolidone (PVP) as solvent, anti-solvent, bridging liquid and polymer, respectively. The main objective of this research to overcome the low fisetin solubility, micromiretic properties and in vitro dissolution. It was prepared using spherical agglomeration method, organic solvent and polymer. Characterization is carried out on morphology particle, drug loading efficiency, solubility and in vitro disolution. XRD studies showed a decrease in crystallinity in agglomerates. The crystals exhibited significantly improved micromeritic properties compared to pure drug. The loading efficiency was in the range of 98.25 ± 1,20 %. The aqueous solubility and dissolution rate of the drug from crystals was significantly increased, 4,45 mg/ml ± 0,31 dan 98,75%, respectively. The SEM studies showed that the crystal posseses a good spherical shape with smooth and regular surface. Conclusion, fisetin was successfully prepared by spherical agglomeration method, with the polyvinylpyrrolidone 5% as polymer, ethanol as good solvent, water as antisolvent and choloform as bridging solvent.. Fisetin increased its solubility and in vitro disolution significantly after spherical agglomeration Keywords: fisetin, spherical crystallization, solubility, in vitro dissolution , micromeritic properties.